Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content:• The Intermediary Role of Sustainable Development in the Relationship Between Good Governance and Performance Improvement: A Case Study of Municipalities in the Gaza Strip (Palestine)Mr. Abdalmoti Mahmoud Albhaisi , Prof. Souad Kamoun Alchouk• The internal and external influences on U.S. policy in the Middle EastMr. Tarek Jarjoura Chahine• The impact of Electronic Human Resource Management (E-HRM) on improving institutional performance at the Ministry of media in RiyadhDr. Shulaywih Hudayris Almutairi• The Relationship Between Team Management and Enhancing Organizational Resilience  in the Municipalities of Northern Gaza Amid the Israeli War (2023–2025)Dr. Mohana Hasen Ebrahim Elmasry• The Impact of Using Artificial Intelligence Technologies on Crowd Management "A Field Study on Employees of the General Department of Crowd Management at the General Authority for the Affairs of the Grand Mosque and the Prophet’s Mosque in Makkah City"Co-Prof. Hassan AbdulQadir Taibah, Mr. Mohammad Omar Agili ,Mr. Mohammad Hashem Khoj• Legislative Protection for Persons with Disabilities in the Saudi System: A Study in Light of Sustainable Development and Vision 2030Dr. Ola Ahmed Gaber Abdallah• Investigating Operational Performance Outcomes and Adopting Sustainable Supply Chain Management Practices in The Health Sector (As a Case Study on NUPCO Company)Dr. Tariq Khidir Eltayeb, Ms. Mona Aedh Hamad Alghamdi
Keywords: The Journal of Economic, Administrative and Legal Sciences